“Nosotras que no escribimos como las demás”: the authorial project of Lucia Etxebarría in light of the prefaces of his works (XXI Century. Spanish Literature and Culture, 2005)
The study is articulated as an invitation to weigh the horizon of possibilities opened bythe hermeneutic approach to the paratextual elements, which help us to demarcaterelationships between the different actors who negotiate in the communicative processes of typeliterary through the prefaces of the works of Lucía Etxebarría.
Keywords: Lucía Etxebarría